Implementation of Location Based Service Method in Design of Housing Location Search Applications in The City of Bengkulu - Arevo Syahputra; Diana Diana; Yuza Reswan; Eka Sahputra (Jurnal Komputer, Informasi dan Teknologi, 2023)
The increase in the number of residents in the city of Bengkulu, in line with the increase in the number of housing being built. The community is conducting a housing search based on information from newspapers and the local community. This is of course especially difficult. For people who come from outside the city of Bengkulu. To overcome this, a housing location search application in Bengkulu City was designed. The designed application can run both on websites and smartphones. This application implements Location Based Service and Google Maps API so that it can display a digital map of Bengkulu City which is equipped with residential location points. If the location point is clicked, the application will display detailed information about the housing.